Modeling the Pedagogical Experience of England as a Factor of Improving the Quality of Training Future Teachers - Abduraxmanovich, Jabbarov Ulugbek (International Journal of Psychosocial Rehabilitation, 2020)
The article is devoted to studying the pedagogical experience of England as the most progressive in Europe and the possibilities of its implementation in the process of improving the preparation of future teachers of English in pedagogical universities of Uzbekistan.